Strenght of Materials - Nhu Phuong Mai (Bach Khoa, 2010)
This text book is designed for students on Mechatronics specification of Advanced programe with 4 credicts. It is also be useful for students on Materials Engineering to fulfill their English on specification. Author expectst that this book will help students who have the passion of learning well this subject to improve their knowledge, as well as to prepar for their Postgraduate Programe abd future job.